Surgical angioplasty for isolated coronary ostial stenosis. - Bortolotti, U (1997)
Patch angioplasty has been reported as a suitable surgical option for patients with isolated coronary ostial stenosis, but controversy still exists concerning its effectiveness. We report the cases of 4 additional patients in whom this procedure was performed, including that of a patient with bilateral ostial stenosis; and we review the literature pertaining to bilateral ostial stenosis. Four patients, 3 with isolated stenosis of the left main coronary ostium and 1 with bilateral ostial stenosis, had direct surgical ostioplasty from January through November 1994. We considered the cause of ostial stenosis to be aortitis (of suspected syphilitic origin) in 1 patient, atherosclerotic plaque in 2 patients, and a fibrous membrane in the 4th. Ostioplasty was performed with a patch of autologous pericardium in 3 patients (fresh pericardium in 2 and glutaraldehyde-fixed in 1) and a patch of saphenous vein in 1. There were no operative deaths. One patient underwent successful reoperation for left main coronary artery restenosis after 3 months. All other patients are asymptomatic at 16, 18, and 24 months postoperatively. In the patient who underwent bilateral ostioplasty, coronary angiography showed patent ostia at 1 year. Surgical ostioplasty should be considered in the treatment of patients who have isolated ostial stenosis but no distal coronary disease. Careful patient selection seems to be a prerequisite for surgical success.